2021
DOI: 10.1002/micr.30701
|View full text |Cite
|
Sign up to set email alerts
|

Combining superficial and deep lymphovenous anastomosis for lymphedema treatment: Preliminary results

Abstract: Background: Superficial lymphovenous anastomosis (LVA) is a widely accepted procedure for treatment of mild-to-moderate lymphedema throughout the body.Anyway, not always are the superficial lymphatic vessels suitable for the anastomosis nor do they provide a sufficient drainage to significantly improve the condition. The continuous progress of supermicrosurgical technique over the last few years and the recent anatomical researches about the deep lymphatic network opened new perspectives for those lymphedema c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 25 publications
(25 reference statements)
0
12
0
1
Order By: Relevance
“…1 . 5 21 22 26 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 …”
Section: Resultsunclassified
“…1 . 5 21 22 26 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 …”
Section: Resultsunclassified
“…Studies were conducted retrospectively, other than 14 performed prospectively. 22,[28][29][30][31]42,47,52,[54][55][56]59,66,84 No randomized control trials (RCTs) were identified. Mean duration of lymphedema symptoms before treatment ranged from 12 months 29,65 to 11.4 years.…”
Section: Resultsmentioning
confidence: 99%
“…27,66,68,71,80 The remaining 41 studies included patients with either primary or secondary lymphedema. [16][17][18][19][20]22,24,[29][30][31][32][33][34][35][36]41,[43][44][45][46][50][51][52][54][55][56][57][58][59]61,67,72,75,76,78,81,82,84,85,88,89 Baseline and post-surgical lymphedema objective assessment were performed in various ways, including circumferential limb measurements in 34 studies, magnetic resonance volumetry in three studies, body weight in one study, body composition analysis (used to determine changes in extracellular fluid (ECF) volume) in one study, perometer limb volumetry in two studies, bioelectrical impedance in one study, computed tomography measurement of subcutaneous fat thickness in one study, lymphoscintigraphy in one study, ICG lymphography in three...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supermicrosurgical lymphaticovenous anastomosis (LVA), which is a minimally invasive bypass surgery that improves lymphedema by channeling the stagnant lymphatic fluid from the lymphatic vessels of the affected limbs into the recipient veins [ 24 , 29 , 30 , 31 , 32 , 33 ], has been accepted as a standard surgical procedure for LLL. Emerging evidence supports the therapeutic benefits of LVA, not only in patients with mild lymphedema, but also in those with more severe conditions [ 31 , 34 , 35 , 36 , 37 ]. However, despite the increasing prevalence of LLL and the potential complications of untreated LLL in older individuals, the effectiveness of LVA for treating secondary LLL in this patient population remains a clinical challenge when considering the unfavorable age- and lymphedema-related lymphatic changes.…”
Section: Introductionmentioning
confidence: 99%